Efektivitas Pelayanan Kesehatan Di Pusat Kesehatan Masyarakat Kasimbar Kecamatan Kasimbar Kabupaten Parigi Moutong - Sari, Jefi Puspita; Nasrullah; Rachmad (JPS: Journal of Publicness Studies, 2025)
The author chose to research the effectiveness of health services at the Kasimbar Community Health Center, Kasimbar District, Parigi Moutong Regency. This research aims to determine the extent of the effectiveness of health services at the Kasimbar Community Health Center. The method used is qualitative research with a descriptive approach, where the selection of informants is carried out purposively. The data used consists of primary and secondary data, with data collection techniques through observation, interviews and documentation. There were six informants involved in this research. The theory used in this research is the theory put forward by Richard M. Steers (2020) which includes four aspects: quality, productivity, work morale, and adaptability. The research results show that the effectiveness of health services at the Kasimbar Community Health Center is good, although it still needs further improvement. The quality aspect is quite good, but facilities and infrastructure need to be improved. The productivity aspect is also good, which can be seen from the discipline of the officers who are always ready to serve. The morale of the officers is also good, even though incentives are given based on group, this does not reduce their enthusiasm. Meanwhile, in the aspect of adaptability, officers have demonstrated good skills in providing services to patients.